A silicon-containing calcium phosphate sintering powder capable of secondary forming and hardening and a preparation method thereof

CN122977832APending Publication Date: 2026-10-27NORTHERN JIANGSU PEOPLES HOSPITAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611284436.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0009]本发明旨在解决部分烧结磷酸钙粉体虽然经X射线衍射检测含有α-TCP晶相,但经破碎和球磨后实际二次硬化能力不足的问题,提供一种高硅源共同烧结及二次机械活化方法,使所得粉体能够重新与水性液体调和,并形成可脱模、可浸水保持且具有实际力学强度的二次硬化体

Benefits of technology

本发明通过硅源组成调控、钙磷硅原料共同高温处理以及烧结后机械活化,使传统高温烧结形成的磷酸钙陶瓷材料重新获得可调和、可塑形和硬化能力,实现烧结型磷酸钙材料由固定陶瓷形态向可再次加工粉体形态的转变。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977832A_ABST
    Figure CN122977832A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of biological medical calcium phosphate material, and discloses a silicon-containing calcium phosphate sintering powder capable of secondary forming and hardening and a preparation method thereof.Calcium source, phosphorus source and silica sol are co-milled in anhydrous ethanol medium, and the obtained activated powder is dried, subjected to high-temperature treatment, cooled, broken and subjected to secondary mechanical activation, so that the activated powder can be mixed with an aqueous liquid and forms a secondary hardened body without compounding other reactive calcium phosphate solid powder in the powder phase.Comparison tests show that the water medium milling sample does not form a stable secondary hardened body, which indicates that the milling medium, raw material composition, heat treatment and mechanical activation state jointly affect the secondary hardening behavior.The obtained hardened body can be completely demolded, maintains the shape after being immersed in water and has a measurable compressive strength, and the main X-ray diffraction peaks before and after hardening are basically maintained.The present application provides a new technical path for the reprocessing, on-site shaping and individual forming of silicon-containing calcium phosphate sintering materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical ceramics and bone repair materials, and in particular to sintered calcium silicate phosphate powder that can be hardened by secondary molding and its preparation method. Background Technology

[0002] Tricalcium phosphate (α-TCP) exhibits hydration reactivity and is a crucial reactive phase in self-curing calcium phosphate bone repair materials. When traditional silicon-free α-TCP powder is mixed with an aqueous liquid, it gradually forms calcium-deficient hydroxyapatite or hydroxyapatite through a dissolution-precipitation process. The newly formed apatite crystals interlock between particles, causing the slurry to solidify and develop mechanical strength. Therefore, current technologies for evaluating the potential hydraulic properties of calcium phosphate powder typically focus first on whether the α-TCP crystalline phase forms and its relative content.

[0003] However, X-ray diffraction is mainly used to identify the main crystalline phase of a material and cannot directly characterize the solubility of the particle surface, the presence of a small amount of amorphous phase, the interface state, or the hydration nucleation conditions. Even if the main crystalline phase is also α-TCP, different high-temperature treatment temperatures, holding times, cooling methods, grain sizes, impurity phase compositions, and post-calcination ball milling histories can cause the powder to exhibit significantly different hydration and agglomeration behaviors. Therefore, "detecting α-TCP" does not equate to "being able to form a stable solidified body."

[0004] Silicon sources are often introduced into calcium phosphate systems to regulate phase stability, sintered structure, and material properties. However, the effect of silicon sources does not change linearly with the amount added. Their content, calculation method, introduction stage, and the liquid medium used can all alter the reaction pathways of calcium, phosphorus, and silicon components during high-temperature processes, as well as the particle interfaces, amorphous phases, and surface reaction states after sintering. Therefore, for silicon-containing calcium phosphate materials, it is still difficult to determine whether they possess secondary hardening capabilities after pulverization and mechanical activation based solely on the α-TCP diffraction peaks in post-sintering XRD.

[0005] In their preliminary research, the inventors discovered that some calcium silicate phosphate materials prepared using a nominally low-silicon substitution formulation, although showing the presence of α-TCP in post-calcination XRD, still failed to form a stable, solidified body that could be completely demolded and retained in water after crushing, secondary ball milling, and mixing with an aqueous liquid. In contrast, the silicon-free α-TCP control in the same test system clearly generated HA and solidified during hydration. This phenomenon reveals a previously overlooked technical contradiction: the crystalline phase composition of the sintered powder may be decoupled from its actual hydraulic activity.

[0006] In further research, the inventors discovered that when silica sol is ball-milled and co-treated at high temperatures with calcium and phosphorus sources before sintering at a relatively high addition level, the resulting silicon-containing co-sintered material, after undergoing crushing and secondary mechanical activation, can be remixed with an aqueous liquid, molded, and hardened. More notably, the resulting solidified body exhibits measurable compressive strength, while the bulk X-ray diffraction patterns remain largely unchanged before and after curing, and the significant α-TCP to HA transformation observed during conventional silicon-free α-TCP hydration is not detected. These results indicate that, under specific composition and processing history, sintered silicon-containing calcium phosphate powder can exhibit secondary hardening behavior distinct from the conventional bulk phase transformation pathway.

[0007] Furthermore, the inventors also observed that sintered powders obtained under different calcium, phosphorus, and silicon raw material ratios and different initial ball milling media conditions may still exhibit significant differences in their secondary forming and hardening performance, even if the α-TCP crystal phase is detected in the main body X-ray diffraction pattern. The specific microscopic reasons for the above differences are not considered necessary limitations for the establishment of the technical solution of this invention.

[0008] Therefore, the field needs to shift from "what crystal phase to obtain" to "how to establish a practically usable secondary hardening capability", and provide a method that can coordinate the silicon source composition, high-temperature co-sintering state and secondary mechanical activation process, so that silicon-containing calcium phosphate materials that have undergone high-temperature treatment can regain the ability to be blended, shaped, demolded, retained in water and form mechanical strength. Summary of the Invention

[0009] This invention aims to solve the problem that although some sintered calcium phosphate powders contain the α-TCP crystalline phase as detected by X-ray diffraction, their actual secondary hardening ability is insufficient after crushing and ball milling. It provides a method for co-sintering with a high silicon source and secondary mechanical activation, so that the resulting powder can be remixed with an aqueous liquid to form a secondary hardened body that can be demolded, retained by immersion in water, and has actual mechanical strength.

[0010] As a first aspect of the present invention, the present invention provides a method for preparing a secondary-curing sintered calcium silicate phosphate powder, comprising the following steps: S1. Take dicalcium phosphate, calcium carbonate, and silica sol, mix them according to a predetermined ratio, wherein the molar ratio of dicalcium phosphate to calcium carbonate is 2:1, and perform a first ball milling treatment using anhydrous ethanol as the liquid medium to fully mix the silicon, calcium, and phosphorus components, forming a uniformly dispersed silicon-calcium-phosphorus composite precursor system. The amount of silica sol added, calculated as SiO2, accounts for 10wt%-35wt% of the total mass of dicalcium phosphate and calcium carbonate solids. S2. The slurry obtained from the first ball milling is dried, crushed, sieved, and kept at 900-1100℃ for 1-3 hours, then heated to 1300-1450℃ and kept at 1-3 hours; after the holding time is completed, it is immediately taken out and rapidly cooled (air-cooled) to room temperature to obtain the co-sintered material containing calcium silicate phosphate. S3. The co-sintered material containing silicon calcium phosphate is crushed and subjected to secondary ball milling or mechanical activation treatment using anhydrous ethanol as the ball milling medium to obtain an activated slurry with secondary reactive activity. S4. The activated slurry is dried, pulverized, and sieved to obtain activated powder with uniform particle size.

[0011] In a preferred embodiment, in S1, the dicalcium phosphate accounts for 36.56wt%-62.67wt% of the mixed raw materials, the calcium carbonate accounts for 13.44wt%-23.04wt% of the mixed raw materials, and the silica sol accounts for 14.30wt%-50.00wt% of the mixed raw materials.

[0012] In a preferred embodiment, the amount of silica sol added in S1, calculated as SiO2, is 10wt%-25wt% of the total mass of dicalcium phosphate and calcium carbonate solids.

[0013] In a preferred embodiment, the dicalcium phosphate in S1 is anhydrous dicalcium phosphate and / or dicalcium phosphate dihydrate; the silica sol is a suspension of nano-SiO2 particles with water as the dispersion medium, a neutral pH, and a solid content of 10wt%-40wt%.

[0014] In a preferred embodiment, the medium used in both the first and second ball milling processes is anhydrous ethanol.

[0015] In a preferred embodiment, the volume ratio of the mixed raw material to anhydrous ethanol in S1 is 1:(1-2); the ball mill is a planetary ball mill, and the grinding media is zirconia balls; the ball mill speed is 200rpm-350rpm, the ball milling time is 1h-4h, and the ball-to-material ratio is 10:1-30:1.

[0016] In a preferred embodiment, the volume ratio of the crushed silicon-containing co-sintered body to anhydrous ethanol in step S3 is 1:1-2; the ball mill is a planetary ball mill, and the grinding media is zirconia balls; the ball mill speed is 250rpm-450rpm, the ball milling time is 2h-6h, and the ball-to-material ratio is 10:1-30:1.

[0017] In a preferred embodiment, the drying temperature in both S2 and S4 is 37℃-70℃, and the drying time is 20h-30h.

[0018] In a preferred embodiment, a 250-300 mesh sieve is used for sieving in S4.

[0019] As a second aspect of the present invention, the present invention provides a silicon-containing calcium phosphate sintered powder prepared by the above method, wherein the main crystal phases in the main body X-ray diffraction patterns before and after secondary hardening both include α-tricalcium phosphate and silicon dioxide, no obvious hydroxyapatite newly formed diffraction peaks were observed, and the compressive strength of the secondary hardened body is not less than 7 MPa.

[0020] As a third aspect of the present invention, the present invention provides the application of the above-mentioned sintered calcium silicate phosphate powder in the preparation of bone defect filling materials, bone cement, plastic bone repair particles, plastic bone repair rods or individualized bone repair components, including using the sintered calcium silicate phosphate powder material as a single inorganic reactive powder, mixing and blending it with an aqueous liquid, and obtaining a secondary hardened body after molding and moist curing.

[0021] In a preferred embodiment, the aqueous liquid is deionized water or an alkaline phosphate aqueous solution, wherein the alkaline phosphate aqueous solution is prepared by dissolving 5-10 g of anhydrous disodium hydrogen phosphate in 100 mL of deionized water. In this application, the disodium hydrogen phosphate aqueous solution is mainly used as an alkaline mixing solution to provide an alkaline environment for the powder-liquid mixing system, and is not added as an additional calcium-phosphorus solid-phase reaction powder.

[0022] As a preferred embodiment, the secondary hardened body can be demolded after being cured in a humid environment at 37°C for more than 0.5 hours, preferably after 12 hours of curing, and then soaked in water for 24 hours to maintain its overall shape, thus obtaining a structurally stable hardened body.

[0023] The beneficial effects of this invention are: This invention enables calcium phosphate ceramic materials formed by traditional high-temperature sintering to regain their malleability, plasticity, and hardening ability through silicon source composition regulation, high-temperature treatment of calcium phosphate and silicon raw materials, and mechanical activation after sintering. This allows sintered calcium phosphate materials to transform from a fixed ceramic form to a reprocessable powder form.

[0024] This invention achieves full mixing of silicon, calcium, and phosphorus components at the microscale by ball milling silica sol together with calcium and phosphorus sources before sintering, and forming a silicon-containing calcium phosphate composite structure during high-temperature treatment. The introduction of silicon sources, along with the ball milling media, high-temperature treatment, and secondary mechanical activation, jointly influence the secondary forming and hardening behavior of the resulting sintered powder.

[0025] The material obtained by this invention, after high-temperature treatment, does not require the addition of other reactive calcium and phosphorus solid powders in the powder phase. It can be obtained as a single inorganic powder that can react with aqueous liquids through secondary mechanical activation, and can be re-blended, molded, and hardened. This simplifies the preparation process of multi-component compounding in traditional bone cement systems.

[0026] The activated powder obtained by this invention can form a secondary hardened body with a complete structure after being mixed with an aqueous liquid, and exhibits certain mechanical properties and water immersion stability; at the same time, the main crystal phase of the material does not show significant changes before and after curing, exhibiting material characteristics that are different from the traditional calcium phosphate hydration hardening process.

[0027] The method of this invention enables sintered calcium silicate phosphate powder to be reconstituted into a powder material with processing capabilities after high-temperature treatment, providing a new technical path for personalized shaping of bone defect repair materials, filling of complex structures, and remolding of multiphase calcium phosphate materials. Attached Figure Description

[0028] Figure 1 This is a schematic diagram of the process flow for the preparation method of the present invention.

[0029] Figure 2 The image shows the XRD pattern of the powder after secondary mechanical activation in Example 1.

[0030] Figure 3 The image shows the XRD pattern of the secondary hardened body from Example 1.

[0031] Figure 4 The image shows the morphology of the powder after mixing, molding, demolding, and immersion in water in Example 1.

[0032] Figure 5 The image shows the XRD pattern of Comparative Example 1 before hydration.

[0033] Figure 6 The image shows the XRD pattern of Comparative Example 1 after hydration.

[0034] Figure 7 This is a picture of the sample after calcination in Comparative Example 3.

[0035] Figure 8 The image shows the XRD pattern of the calcined sample of Comparative Example 3.

[0036] Figure 9 The image shows the XRD pattern of the calcined powder of Comparative Example 4.

[0037] Figure 10 The image shows the state after firing in Comparative Example 4 and its state after secondary molding failure. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention in any way. It should be noted that, unless otherwise specified, the following embodiments and features can be combined with each other. It should also be understood that the terminology used in the embodiments of this invention is for describing specific implementation schemes and not for limiting the scope of protection of this invention.

[0039] When a range of values ​​is given, it should be understood that, unless otherwise stated in this invention, the two endpoints of each range and any value between the two endpoints may be selected.

[0040] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly used in the field to which this invention pertains. The terminology used to describe this invention is intended only to describe a particular implementation and is not intended to limit the scope of the teachings. This invention can be implemented using any prior art methods, apparatus, and materials similar to or equivalent to those described, used, or made in the embodiments of this invention.

[0041] The term “and / or” as used herein should be understood to mean any one of the options or any combination of two or more of the options.

[0042] As used herein, the term "about" indicates a range of ±20% of the following value. The term "high silicon source" as used in this invention refers to a silica sol with an addition amount of 10 wt% or more of the total mass of the calcium hydrogen phosphate and calcium carbonate solids, calculated as SiO2. In some embodiments, the term "about" indicates a range of ±10% of the following value. In some embodiments, the term "about" indicates a range of ±5% of the following value.

[0043] The following embodiments and accompanying drawings are provided to aid in understanding the present invention. However, it should be understood that these embodiments are for illustrative purposes only and do not constitute any limitation. The actual scope of protection of the present invention is set forth in the claims. It should be understood that any modifications and changes can be made without departing from the spirit of the present invention. Unless otherwise specified, the raw materials used in the embodiments are all commercially available products in the art, their specifications are conventional specifications in the art, and the methods used are conventional methods in the art. The instruments and equipment used in the embodiments are conventional instruments and equipment in the art.

[0044] Example 1 like Figure 1 As shown, this embodiment provides a method for preparing a sintered calcium silicate phosphate powder that can be hardened by secondary molding, including the following steps: Step 1: Weighing raw materials: Mix anhydrous dicalcium phosphate, calcium carbonate and silica sol in a mass percentage of 55.0%, 20.2% and 24.8% respectively to obtain mixed raw materials; the silica sol is a suspension of nano-SiO2 particles with water as the dispersion medium, with a neutral pH and a solid content of 40wt%.

[0045] Step 2, initial anhydrous ethanol ball milling: The mixed raw materials and anhydrous ethanol are added to a planetary ball mill at a volume ratio of 1:1 for wet ball milling to fully mix the calcium, phosphorus and silicon components and form a uniformly dispersed silicon-calcium-phosphorus precursor system; the ball milling speed is 350 rpm, the ball milling time is 2 hours, and the ball milling media is zirconia balls.

[0046] Step 3, Precursor Drying Treatment: Take out the slurry obtained from the first ball milling and place it in an oven for drying treatment to remove the liquid medium and obtain the dried silicon-calcium-phosphorus precursor powder; wherein, the drying temperature is 60℃ and the drying time is 24h.

[0047] Step 4, Pretreatment and High-Temperature Sintering: The dried precursor powder is placed in an alumina crucible for high-temperature sintering, specifically as follows: (1) Heat to 1000℃ at a heating rate of 5℃ / min and keep at 1000℃ for 2h; (2) Continue heating at a rate of 5℃ / min to 1400℃ and hold at 1400℃ for 2 hours; remove and cool rapidly. During sintering, the gradient heating process is conducive to the gradual release of residual moisture and volatile components in the precursor, and promotes the transformation of calcium and phosphorus phases and the stability of grain structure, thereby reducing the risk of material cracking during high-temperature sintering.

[0048] Step 5: Crushing and Secondary Mechanical Activation of Sintered Materials: After cooling the high-temperature sintered calcium silicate phosphate material to room temperature, it is crushed. Anhydrous ethanol is used as the ball milling medium. The sintered material and anhydrous ethanol are added to a planetary ball mill at a volume ratio of 1:1 for wet ball milling. An activated slurry is obtained. The secondary ball milling speed is 350 rpm, and the milling time is 3 hours.

[0049] Step Six: Drying, pulverizing, sieving, and secondary molding of activated powder: The activated slurry obtained from the secondary ball milling is dried, pulverized, and sieved. The drying temperature is 40℃ and the time is 24h. After passing through a 300-mesh sieve, activated powder with uniform particle size is obtained. Then, the activated powder is mixed with an aqueous solution prepared by dissolving 7 g of anhydrous disodium hydrogen phosphate in 100 mL of deionized water at a powder-to-liquid ratio of 3 g / mL. The mixture is then placed in a mold for molding and cured in a humid environment at 37℃ for 12h to obtain a secondary hardened body.

[0050] Figure 2The image shows the XRD pattern of the powder after secondary mechanical activation in Example 1. The main crystalline phases include α-TCP and SiO2. Figure 3 Its XRD pattern after secondary hardening, and Figure 2 In comparison, the main crystal phase remained essentially unchanged, and no new identifiable HA characteristic diffraction peaks appeared compared to before the secondary hardening. Table 1 shows the compressive strength test results of the secondary hardened body in Example 1. The compressive strength of the six parallel samples ranged from 6.04 to 9.25 MPa, with an average compressive strength of (7.83 ± 1.24) MPa, indicating that the obtained secondary hardened body has measurable compressive strength and a certain degree of mechanical stability.

[0051] Table 1. Compressive strength test results of the secondary hardened body in Example 1

[0052] Figure 4 The secondary molding results of Example 1 are shown, in which Figure 4 (a) is the sample after the activated powder has been mixed and shaped. Figure 4 (b) shows the state of the hardened body after immersion in water. The sample maintained its intact shape after immersion in water, indicating that it has a stable secondary hardening ability. The obtained hardened body, after being demolded, was immersed in water for 24 hours and still maintained its overall shape.

[0053] Example 2 This embodiment provides a method for preparing sintered calcium silicate phosphate powder that can be hardened by secondary molding, including the following steps: Step 1: Weighing raw materials: Mix anhydrous dicalcium phosphate, calcium carbonate and silica sol in a mass percentage of 43.9%, 16.1% and 40.0% respectively to obtain mixed raw materials; the silica sol is a suspension of nano-SiO2 particles with water as the dispersion medium, with a neutral pH and a solid content of 35wt%.

[0054] Step 2, initial anhydrous ethanol ball milling: The mixed raw materials and anhydrous ethanol are added to a planetary ball mill at a volume ratio of 1:1 for wet ball milling to fully mix the calcium, phosphorus and silicon components and form a uniformly dispersed silicon-calcium-phosphorus precursor system; the ball milling speed is 300 rpm, the ball milling time is 1 hour, and the ball milling media is zirconia balls.

[0055] Step 3: Precursor drying treatment: The slurry obtained from the first ball milling was taken out and placed in an oven for drying to remove the liquid medium, resulting in dried silicon-calcium-phosphorus precursor powder; the drying temperature was 60℃ and the drying time was 24h.

[0056] Step 4, Pretreatment and High-Temperature Sintering: The dried precursor powder is placed in an alumina crucible for high-temperature sintering, specifically as follows: (1) Heat to 1000℃ at a heating rate of 5℃ / min and keep at 1000℃ for 2h; (2) Continue heating at a rate of 5℃ / min to 1300℃ and hold at 1300℃ for 3 hours; remove and cool rapidly. Step 5: Crushing and Secondary Mechanical Activation of Sintered Materials: After cooling the high-temperature sintered calcium silicate phosphate material to room temperature, it is crushed. Anhydrous ethanol is used as the ball milling medium. The sintered material and anhydrous ethanol are added to a planetary ball mill at a volume ratio of 1:1 for wet ball milling. An activated slurry is obtained. The secondary ball milling speed is 350 rpm, and the milling time is 3 hours.

[0057] Step Six: Drying, pulverizing, sieving, and secondary molding of activated powder: The activated slurry obtained from the secondary ball milling is dried, pulverized, and sieved. The drying temperature is 40℃ and the time is 24h. After passing through a 290-mesh sieve, activated powder with uniform particle size is obtained. Then, the activated powder is mixed with an aqueous solution prepared by dissolving 5 g of anhydrous disodium hydrogen phosphate in 100 mL of deionized water at a powder-to-liquid ratio of 3 g / mL. The mixture is then placed in a mold for molding and cured in a humid environment at 37℃ for 0.5h before being completely demolded to obtain a secondary hardened body.

[0058] Example 3 This embodiment provides a method for preparing sintered calcium silicate phosphate powder that can be hardened by secondary molding, including the following steps: Step 1: Weighing raw materials: Mix anhydrous dicalcium phosphate, calcium carbonate and silica sol in a mass percentage of 43.9%, 16.1% and 40.0% respectively to obtain mixed raw materials; the silica sol is a suspension of nano-SiO2 particles with water as the dispersion medium, with a neutral pH and a solid content of 35wt%.

[0059] Step 2, initial anhydrous ethanol ball milling: The mixed raw materials and anhydrous ethanol are added to a planetary ball mill at a volume ratio of 1:1 for wet ball milling to fully mix the calcium, phosphorus and silicon components and form a uniformly dispersed silicon-calcium-phosphorus precursor system; the ball milling speed is 300 rpm and the ball milling time is 3 hours, and the ball milling media is zirconia balls.

[0060] Step 3: Precursor drying treatment: The slurry obtained from the first ball milling was taken out and placed in an oven for drying to remove the liquid medium, resulting in dried silicon-calcium-phosphorus precursor powder; the drying temperature was 60℃ and the drying time was 24h.

[0061] Step 4, Pretreatment and High-Temperature Sintering: The dried precursor powder is placed in an alumina crucible for high-temperature sintering, specifically as follows: (1) Heat to 1000℃ at a heating rate of 5℃ / min and keep at 1000℃ for 2h; (2) Continue heating at a rate of 5℃ / min to 1300℃ and hold at 1300℃ for 2 hours; remove and cool rapidly. Step 5: Crushing and Secondary Mechanical Activation of Sintered Materials: After cooling the high-temperature sintered calcium silicate phosphate material to room temperature, it is crushed. Anhydrous ethanol is used as the ball milling medium. The sintered body and anhydrous ethanol are added to a planetary ball mill at a volume ratio of 1:1 for wet ball milling. An activated slurry is obtained. The secondary ball milling speed is 250 rpm, and the milling time is 3 hours.

[0062] Step Six: Drying, pulverizing, sieving, and secondary molding of activated powder: The activated slurry obtained from the secondary ball milling is dried, pulverized, and sieved. The drying temperature is 40℃ and the time is 24h. After passing through a 300-mesh sieve, activated powder with uniform particle size is obtained. Then, the activated powder is mixed with deionized water at a powder-to-liquid ratio of 3 g / mL, placed into a mold for molding, and cured in a humid environment at 37℃ for 6h to obtain a secondary hardened body.

[0063] Comparative Example 1 Compared to Example 1, Comparative Example 1 did not add silica sol in step one, and pure water was used as the ball milling medium for the first ball milling. The remaining raw material ratios and process conditions were consistent with those of Example 1. The obtained silicon-free α-TCP powder could solidify and harden after being mixed with an aqueous liquid; obvious hydroxyapatite diffraction peaks appeared in the X-ray diffraction pattern after hydration, indicating that the silicon-free α-TCP powder formed a hardened body through the traditional α-TCP hydration transformation path.

[0064] Figure 5 and Figure 6 The XRD patterns of Comparative Example 1 (silicon-free α-TCP) before and after hydration are shown. The presence of a distinct HA diffraction peak after hydration indicates that solidification and hardening are primarily achieved through the conversion of α-TCP to HA.

[0065] Comparative Example 2 Compared to Example 1, Comparative Example 2 used the same raw material ratio as Example 1, but replaced the initial ball milling media with pure water instead of anhydrous ethanol. The remaining conditions for high-temperature treatment, crushing, secondary mechanical activation, sieving, and molding evaluation remained the same. The resulting activated powder, when mixed with an aqueous liquid, could not form a stable, secondary hardened body that could be completely demolded and maintain its shape.

[0066] Comparative Example 3 While maintaining a calcium carbonate to dicalcium phosphate ratio of 1:2, silica sol with a solid content of 35 wt% was added. The amount of silicon source added (based on SiO2) was approximately 20 wt% of the total solid mass of the calcium and phosphorus sources. Pure water was used as the initial ball milling medium. The remaining processing and molding evaluation conditions were the same as in Example 1. The resulting powder, after mixing with an aqueous liquid, still could not form a stable secondary hardened body. This result indicates that, under water milling conditions, simply increasing the amount of silicon source added did not achieve the same secondary hardening effect as in Example 1.

[0067] Figure 7 and Figure 8 The macroscopic morphology and XRD pattern of the calcined sample of Comparative Example 3 are shown respectively. Figure 7 The sample shows that it formed a white sintered block after high-temperature treatment; Figure 8 The sample, after firing, showed the simultaneous presence of α-TCP and HA crystalline phases. The sample failed to harden stably even after secondary mechanical activation, indicating that the presence of the α-TCP crystalline phase is insufficient to guarantee the material's ability to undergo secondary hardening.

[0068] Comparative Example 4 While maintaining a calcium carbonate to dicalcium phosphate ratio of 1:2, the amount of silica sol added, calculated as SiO2, was approximately 5 wt% of the total mass of the dicalcium phosphate and calcium carbonate solids, lower than the 10 wt% lower limit specified in this invention, thus serving as a low-silicon source comparative example. Anhydrous ethanol was used as the medium for the initial ball milling. The remaining drying, high-temperature treatment, rapid cooling, crushing, secondary mechanical activation, drying, pulverizing, sieving, and molding curing conditions were as described in Example 1.

[0069] Figure 9 The XRD pattern of the calcined powder of Comparative Example 4 shows that it contains the α-TCP crystalline phase. Figure 10 The results of its secondary molding were shown, in which Figure 10 (a) is the sintered block. Figure 10 (b) shows the state of the sintered material after crushing, secondary mechanical activation, and mixing with an aqueous liquid. In the right figure, the material is in a loose state and has not formed a stable hardened body. This indicates that the detection of the α-TCP crystal phase does not necessarily mean that the material has secondary hardening ability. This result shows that when the amount of silicon source added is lower than the lower limit specified in this invention, even if the α-TCP crystal phase is present in the sintered powder, the same secondary hardening ability as in Examples 1-3 cannot be obtained.

[0070] Mechanical property testing Compressive strength tests were performed on the example samples that formed complete hardened bodies and the silicon-free α-TCP positive control samples. The resulting hardened bodies were prepared as cylindrical specimens with a diameter of 4 mm × 9 mm and tested according to GB / T 8489—2006 "Test Method for Compressive Strength of Fine Ceramics". Referring to Table 1, the strengths of the six parallel specimens in Example 1 were 9.25 MPa, 6.04 MPa, 8.92 MPa, 7.32 MPa, 7.03 MPa, and 8.43 MPa, with an average compressive strength of (7.83 ± 1.24) MPa. Comparative Examples 2 and 3 were not tested for compressive strength because they could not form stable secondary hardened bodies.

[0071] Technical Logic and Conclusion Analysis The technical logic of this invention consists of three interrelated experimental phenomena: First, silicon-free α-TCP powder can achieve conventional hydration hardening accompanied by significant hydroxyapatite formation, indicating that the blending and curing conditions used in this application can support the coagulation of hydration-active α-TCP. Second, in Comparative Example 4, the silicon source addition amount, calculated as SiO2, is approximately 5 wt%, lower than the 10 wt% lower limit specified in this invention. Although the resulting sintered powder contains the α-TCP crystalline phase, it cannot form a stable secondary hardened body after secondary mechanical activation. In Examples 1-3, the silicon source addition amount is within the range specified in this invention, and the resulting sintered material can be re-formed and hardened after secondary mechanical activation. Silica sol with a higher silicon source addition amount and calcium phosphate raw material are ball-milled together in anhydrous ethanol medium and subjected to high-temperature treatment, and after secondary mechanical activation, they can be re-formed and hardened, forming a secondary hardened body with measurable compressive strength while maintaining the main body X-ray diffraction pattern. The above results collectively indicate that whether sintered powder can achieve secondary hardening capability is related to the combination of silicon source addition, raw material composition, ball milling media, high-temperature treatment history, and secondary mechanical activation state, and cannot be judged solely based on α-TCP diffraction peaks.

[0072] Further comparative results show that: in Comparative Example 2, the sample with a similar silicon source ratio using water as the initial ball milling medium could not form a stable secondary hardened body; in Comparative Example 3, even after increasing the silicon source addition (based on SiO2) to approximately 20 wt% under water milling conditions, the resulting powder still could not achieve stable secondary hardening; in Comparative Example 4, when using a silicon source addition of approximately 5 wt%, which is lower than the lower limit specified in this invention, a stable secondary hardened body was not obtained under anhydrous ethanol medium conditions. These results indicate that the secondary hardening performance of the obtained powder is not independently determined by the silicon source content, α-TCP crystal phase, or any single nominal composition, but is related to a combination of raw material composition, initial ball milling medium, high-temperature treatment history, and secondary mechanical activation state.

[0073] Therefore, the technical contribution of this invention lies in constructing a composition-heat treatment-mechanical activation combination that enables sintered calcium silicate phosphate powder to obtain secondary hardening ability, providing a new conversion path between sintered ceramic materials and plastic self-curing materials.

Claims

1. A method for preparing a sintered calcium silicate phosphate powder that can be hardened by secondary molding, characterized in that, Includes the following steps: S1. Take dicalcium phosphate, calcium carbonate, and silica sol, mix them in a predetermined ratio, wherein the molar ratio of dicalcium phosphate to calcium carbonate is 2:1, and perform a first ball milling treatment using anhydrous ethanol as the liquid medium to fully mix the silicon, calcium, and phosphorus components, forming a uniformly dispersed silicon-calcium-phosphorus composite precursor system. The amount of silica sol added, calculated as SiO2, accounts for 10wt%-35wt% of the total mass of dicalcium phosphate and calcium carbonate solids. S2. The slurry obtained from the first ball milling is dried. The dried precursor is crushed and sieved, and then kept at 900-1100 ℃ for 1-3 h. Then the temperature is raised to 1300-1450 ℃ and kept for 1-3 h. After the holding time is completed, it is immediately taken out and rapidly cooled to room temperature to obtain the co-sintered material containing calcium silicate phosphate. S3. The co-sintered material containing silicon calcium phosphate is crushed and subjected to secondary ball milling or mechanical activation treatment using anhydrous ethanol as the ball milling medium to obtain an activated slurry with secondary reactive activity. S4. The activated slurry is dried, pulverized and sieved to obtain activated powder with uniform particle size.

2. The preparation method according to claim 1, characterized in that, In S1, the dicalcium phosphate accounts for 36.56wt%-62.67wt% of the mixed raw materials, the calcium carbonate accounts for 13.44wt%-23.04wt% of the mixed raw materials, and the silica sol accounts for 14.30wt%-50.00wt% of the mixed raw materials. The above raw material proportions should meet the requirement that, based on SiO2, the amount of silica sol added accounts for 10wt%-35wt% of the total mass of dicalcium phosphate and calcium carbonate solids.

3. The preparation method according to claim 1, characterized in that, The amount of silica sol added in S1, calculated as SiO2, is 10wt%-25wt% of the total mass of dicalcium phosphate and calcium carbonate solids; The dicalcium phosphate is anhydrous dicalcium phosphate and / or dicalcium phosphate dihydrate. The silica sol is a suspension of nano-SiO2 particles with water as the dispersion medium, a neutral pH, and a solid content of 10wt%-40wt%.

4. The preparation method according to claim 1, characterized in that, The medium used in both the first and second ball milling processes was anhydrous ethanol.

5. The preparation method according to claim 1, characterized in that, The volume ratio of the mixed raw material to anhydrous ethanol in S1 is 1:(1-2); the ball mill is a planetary ball mill, and the grinding media is zirconia balls; the ball mill speed is 200rpm-350rpm, the ball milling time is 1h-4h, and the ball-to-material ratio is 10:1-30:

1. The volume ratio of the crushed silicon-containing co-sintered body to anhydrous ethanol in S3 is 1:1-2; the ball mill is a planetary ball mill, and its grinding media is zirconia balls; the ball mill speed is 250rpm-450rpm, the ball milling time is 2h-6h, and the ball-to-material ratio is 10:1-30:

1.

6. The preparation method according to claim 1, characterized in that, In both S2 and S4, the drying temperature was 37℃-70℃ and the drying time was 20h-30h. S4 uses a 250-300 mesh sieve for sieving.

7. A sintered calcium silicate phosphate powder capable of secondary molding and hardening, characterized in that, Prepared by the preparation method of any one of claims 1-6, the main crystalline phases of the silicon-containing calcium phosphate sintered powder material in the main body X-ray diffraction patterns before and after secondary hardening both include α-tricalcium phosphate and silicon dioxide, and no obvious hydroxyapatite newly formed diffraction peaks were observed. According to GB / T 8489—2006, the average compressive strength of the secondary hardened body is not less than 7 MPa.

8. The application of the secondary-curing sintered calcium silicate phosphate powder of claim 7 in the preparation of bone defect filling materials, bone cement, malleable bone repair particles, malleable bone repair rods, or personalized bone repair components, characterized in that, This includes mixing the silicon-containing calcium phosphate sintered powder material as a single inorganic reactive powder with an aqueous liquid, followed by molding and moist curing to obtain a secondary hardened body.

9. The application according to claim 8, characterized in that, The aqueous liquid is deionized water or an alkaline phosphate aqueous solution; the alkaline phosphate aqueous solution is prepared by dissolving 5-10 g of anhydrous disodium hydrogen phosphate in 100 mL of deionized water; the powder-to-liquid ratio of the activated powder to the aqueous liquid is 2-4 g / mL.

10. The application according to claim 8, characterized in that, The secondary hardened body can be demolded after being cured in a humid environment at 37°C for more than 0.5 hours, and preferably cured for 12 hours. After soaking in water for 24 hours, it maintains its overall shape and obtains a structurally stable hardened body.